2010
DOI: 10.1017/s175173111000039x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain type and processing method on rumen fermentation and milk rumenic acid production

Abstract: It was hypothesized that differences in starch degradability account for observed differences in rumen vaccenic acid (t11-18:1) and milk rumenic acid (RA) concentrations. To test this hypothesis, starch degradability was varied through grain source and by processing. Eight Holstein cows in mid-lactation were assigned to two 4 3 4 Latin squares with four 21-day periods and four diets: dry rolled barley, ground barley, dry rolled corn and ground corn. Diets contained similar starch content and were supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 79 publications
(102 reference statements)
6
28
1
Order By: Relevance
“…The greater proportions of 18:3n-3 and its BH intermediates (e.g., trans-13 + 14 and -15 18:1, and trans-9 cis-12 and trans-11 cis-15 18:2) in steers fed barley compared with those fed maize are consistent with previous results examining the effects of these cereal grains on the composition of rumen BH-derived FA (Mohammed et al, 2010;Toral et al, 2014). However, unlike reported in these studies, the starch source had no effect on the concentration of 18:2n-6 and total trans 18:1, which might exclude a general inhibition of BH by the lower ruminal pH values (Fuentes et al, 2011).…”
Section: Effect Of Dietary Factors On the Ruminal Fatty Acids Profilesupporting
confidence: 90%
See 1 more Smart Citation
“…The greater proportions of 18:3n-3 and its BH intermediates (e.g., trans-13 + 14 and -15 18:1, and trans-9 cis-12 and trans-11 cis-15 18:2) in steers fed barley compared with those fed maize are consistent with previous results examining the effects of these cereal grains on the composition of rumen BH-derived FA (Mohammed et al, 2010;Toral et al, 2014). However, unlike reported in these studies, the starch source had no effect on the concentration of 18:2n-6 and total trans 18:1, which might exclude a general inhibition of BH by the lower ruminal pH values (Fuentes et al, 2011).…”
Section: Effect Of Dietary Factors On the Ruminal Fatty Acids Profilesupporting
confidence: 90%
“…The meat and milk from ruminants contain a high proportion of saturated FA but also some BH intermediates, such as cis-9 trans-11 conjugated linoleic acid (CLA), with potentially health-promoting properties for consumers (Shingfield et al, 2008). Low pH has been shown to reduce BH of linoleic and linolenic acids in continuous culture of ruminal fluid (Fuentes et al, 2011) and a limited saturation of trans 18:1 intermediates to 18:0 because of a more acute rumen pH drop with barley than maize starch has been observed (Mohammed et al, 2010). Heating treatments may also restrain the BH of dietary FA, although results are not always consistent (e.g., PrivĂ© et al, 2010;TroegelerMeynadier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ingredient composition of the concentrate mixture in the present study contained 97% barley. Barley is more fermentable in the rumen in comparison to other diets like corn (Granzin 2004;Lanzas et al 2007;Mohammed et al 2010) and therefore increased ruminal TVFA concentration (Khorasani et al 2001;Au et al 2010;Julien et al 2010) was observed. Higher concentration of TVFA production in group 2 is due to concentrate feeding, and this led to a decrease in ruminal pH both at 0 and 4 h of feeding concentrate.…”
Section: Discussionmentioning
confidence: 97%
“…In this respect, wheat had a lower proportion of NDF (Table 1), and it is well documented that wheat has higher starch content than oats (Shewry, 2009). However, the pH of the rumen is primarily influenced by the fermentable carbohydrate in the diet, and the amount and source of starch and/or the rate of ruminal degradation of starch affects biohydrogenation in the rumen (Mohammed et al, 2010). Wheat grain reduces the ruminal pH and is used to induce subacute ruminal acidosis (SARA); subacute ruminal acidosis results in changes of the fermentation pattern in the rumen, with possible changes in the production of fatty acids (Enjalbert et al, 2008).…”
Section: Intramuscular Fatty Acid Compositionmentioning
confidence: 96%